NAD+ metabolism restriction boosts high-dose melphalan efficacy in patients with multiple myeloma - Debora Soncini; Pamela Becherini; Francesco Ladisa; Silvia Ravera; Adithya Chedere; Elisa Gelli; Giulia Giorgetti; Claudia Martinuzzi; Francesco Piacente; Luca Mastracci; Claudia Veneziano; Gianluca Santamaria; et al. (Blood Advances)
Abstract: Elevated levels of the NAD+-generating enzyme nicotinamide phosphoribosyltransferase (NAMPT) are a common feature across numerous cancer types. Accordingly, we previously reported pervasive NAD+ dysregulation in multiple myeloma (MM) cells in association with upregulated NAMPT expression. Unfortunately, albeit being effective in preclinical models of cancer, NAMPT inhibition has proven ineffective in clinical trials because of the existence of alternative NAD+ production routes using NAD+ precursors other than nicotinamide. Here, by leveraging mathematical modeling approaches integrated with transcriptome data, we defined the specific NAD+ landscape of MM cells and established that the Preiss-Handler pathway for NAD+ biosynthesis, which uses nicotinic acid as a precursor, supports NAD+ synthesis in MM cells via its key enzyme nicotinate phosphoribosyltransferase (NAPRT). Accordingly, we found that NAPRT confers resistance to NAD+-depleting agents. Transcriptomic, metabolic, and bioenergetic profiling of NAPRT-knockout (KO) MM cells showed these to have weakened endogenous antioxidant defenses, increased propensity to oxidative stress, and enhanced genomic instability. Concomitant NAMPT inhibition further compounded the effects of NAPRT-KO, effectively sensitizing MM cells to the chemotherapeutic drug, melphalan; NAPRT added-back fully rescues these phenotypes. Overall, our results propose comprehensive NAD+ biosynthesis inhibition, through simultaneously targeting NAMPT and NAPRT, as a promising strategy to be tested in randomized clinical trials involving transplant-eligible patients with MM, especially those with more aggressive disease.